EVALUASI KEBIJAKAN KEUANGAN PUBLIK DALAM TINJAUAN ISLAM - Naerul Kiky Aprianto (Institut Binamadani Indonesia, 2021)
The economic crisis in Indonesia is caused by poorly managed governance procedures. As a result, problems such as corruption, collusion and nepotism are difficult to eradicate, difficult-to-run law enforcement issues, monopolies in economic activities, and poor quality of service to society. It is necessary to evaluate public financial policy to measure the success and failure of the implementation of a policy. Using review literature, this study aims to analyze the evaluation of public financial policy in an Islamic perspective. In the Islamic review, evaluation of public financial policy can be done through the role of the state in the form of prophetic mission transformation, namely the implementation of teachings so that the government can carry out its role and function in building communities and directed to achieve maqashid syari'ah, so that it will have an impact on the achievement of falah or the welfare of the community in the world and the hereafter.